Mathematical analysis on the effectiveness of coagulation using aluminium sulphate and Moringa Oleifera as coagulant / Najwa Mat Yasin - Mat Yasin, Najwa (2016)
Water is an important element in 21st century as this resource has becomes increasingly polluted. Despite the importance of water for human consumption and development, deterioration of this natural resource is occurring at a critical stage. Population and water resources are closely related as the higher growth rate, the higher demand for clean water supply. With the current water shortage scenario, it is an urgent task to find an alternative in treating the surface water for contingency plan. Shah Alam is one of the examples of modern and a rapid centre of urbanization. There are two lakes which can be foreseen as the potential for water supply for nearby community which are Taman Tasik Shah Alam Seksyen 2 and Taman Tasik Shah Alam Seksyen 7 respectively. Coagulation is the significant stage in conventional drinking water treatment process. However the normal used of alum has been discovered to have many drawbacks which affected the human health. Hence this study is considered to use natural coagulant as an alternative as this substance is environmental friendly without reducing the human health. The investigation of the coagulation process was conducted by using lake water which is aimed to use the natural coagulant for the treatment of this lake water to be used as drinking water supply. Studies on coagulation process were conducted using alum comparing with Moringa Oleifera at concentration (10g/L, 20g/L, 30g/L). This research analysis involved the parameters of suspended solids, colour, turbidity, pH, nitrite, nitrate, phosphorus, and COD. Samples were collected from Taman Tasik Shah Alam Seksyen 2 and Taman Tasik Shah Alam Seksyen 7. Further evaluation on the coagulation process was conducted through a series of Mathematical calculation for comparing alum and Moringa Oleifera using Stoichiometric Analysis and First Order rate of reaction.